(untitled) (Comillas Journal of International Relations, 2023)
This paper aims to analyze Spanish international aid in Sub-Saharan Africa and its different fields of action. The relations between Spain and Africa are framed in the III Africa Plan, published in 2019, that pursues a rapprochement of Spain to the African continent seeking common interests and interacting with the different Spanish actors present in it. More specifically, this paper aims to focus on the relations between Spain and Equatorial Guinea since the latter’s independence in 1968, and how these relations have developed through the Spanish international aid. Since 2007, Spanish aid to Equatorial Guinea has been drastically reduced, and it has ceased to be the main donor since 2010. This article starts from two hypotheses. The first is that since colonial independence, diplomatic relations between Equatorial Guinea and Spain have mainly framed within the scope of international aid. The second, which depends on the first, seeks to understand if Equatorial Guinea is a preferential partner of Spanish aid, and if Spain remains its main aid partner. In this sense, one of the main objectives of this research is to evaluate both the real impact of Spanish Cooperation in Equatorial Guinea and the number of projects, the amounts of money and the different ways in which this relationship has developed.